Soy Protein Alleviates Malnutrition in Weaning Rats by Regulating Gut Microbiota Composition and Serum Metabolites - Wei, Zuchen; Zhou, Nong; Zou, Liang; Shi, Zhenxing; Dun, Baoqing; Ren, Guixing; Yao, Yang (Frontiers in Nutrition, 2021)
Dietary intervention with plant protein is one of the main methods used to lessen symptoms of malnutrition. Supplementary soy protein to undernourished weaning rats for six weeks significantly increased their body weight gain. After intervention, the total short-chain fatty acids (SCFAs) level was restored to 1512.7 μg/g, while the level was only 637.1 μg/g in the 7% protein group. The amino acids (valine, isoleucine, phenylalanine, and tryptophan) increased in the colon, and vitamin B6 metabolism was significantly influenced in malnutrition rats. The tryptophan and glycine-serine-threonine pathways were elevated, leading to an increase in the level of tryptophan and 5-hydroxytryptophan (5-HTP) in the serum. In addition, the relative abundance of Lachnospiraceae_NK4A136_group and Lactobacillus increased, while Enterococcus and Streptococcus decreased compared to undernourished rats. Overall, soy protein improved the growth of rats with malnutrition in early life by regulating gut microbiota and metabolites in the colon and serum.